125 Evaluation of titin cardiomyopathy in patients with dilated cardiomyopathy reveals a blunted hypertrophic response, an early arrhythmic risk and a significant interaction with alcohol. (5th June 2017) - Tayal, Upasana; Buchan, Rachel; Whiffin, Nicola; Newsome, Simon; Walsh, Roddy; Barton, Paul; Ware, James; Cook, Stuart; Prasad, Sanjay
Abstract : Background: Titin truncating variants (TTNtv), found in~10%–20% of dilated cardiomyopathy (DCM), are notable for variable penetrance and expressivity. We evaluated whether TTNtv DCM patients had distinct phenotypic features, which may influence disease outcomes. Methods: Prospectively recruited DCM patients underwent comprehensive clinical evaluation, cardiac MRI and TTN sequencing. Results: Overall, 572 subjects, 388 men (67.8%), mean age 53.5±14.4 years, were recruited. TTNtv were found in 56 patients (9.8%) and were associated with lower indexed LV mass (LVMi) and thinner LV walls, in the absence of differences in LV volumes after adjusting for clinical covariates (LVMi 83.1 vs. 94.0g/m 2, p=0.008; max. LV wall thickness 9.1 vs. 10.1 mm, p=0.003; indexed LV end diastolic volume 122.7 vs. 131.3mls/m 2, p=0.07). 196/572 patients (34%) had atrial fibrillation or ventricular arrhythmia at recruitment. Adjusting for age, gender, baseline ventricular function, and left atrial volume, TTNtv independently associated with early arrhythmic burden (adjusted OR 2.90, CI 1.48 to 5.77, p=0.002). On sensitivity analysis, this association remained significant after exclusion of 12 patients with rare LMNA variants (adjusted OR 2.88, CI 1.45 to 5.81, p=0.003). TTNtv alone did not predict LVEF but in the presence of a history of alcohol excess, LVEF was reduced by 17.5% (p<0.0001), independently of other predictors of LVEF (age, gender, NYHA class, mid-wall fibrosis, and a family history of NIDCM). Conclusions: These data demonstrate that DCM due to TTNtv is associated with a blunted hypertrophic response, highlighting possible disease mechanisms. We also demonstrate that TTNtv are independently predictive of early arrhythmia and show a significant gene-environmental interaction between TTNtv and alcohol, which may inform risk stratification.